The Kinship Terminology and Practice of Bataknese: A Sociolinguistics Approach - Pandiangan, Bobby Samuel (Jambura Journal of English Teaching and Literature, 2024)
This research aims to describe the kinship terminology of four Bataknese tribes: Toba Batak, Karo Batak, Simalungun Batak and Pak-Pak Batak. There were four selected participants, who were native and used kinship terms in family. A questionnaire with 56 questions asking about the kinship terminology and 6 questions asking about the practice of kinship was used as an instrument of this research. The result of this research showed even though from the same Batak tribe, but the kinship terms of the four Batakneses are varied. Simalungun Batak and Toba batak have the most vary terms with 31 in total. Moreover, Bataknese still practice the kinship terminology of Bataknese itself than the national one. Additionally, the society of Bataknese agreed that using Bataknese kinship terminology was a way of respecting family members. In conclusion, Bataknese society still practice and maintain their kinship terminology to strengthen the relationship of the family members.